2016
DOI: 10.1186/s12995-016-0123-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cell-free DNA for evaluating genotoxic damage from occupational exposure to car paints

Abstract: BackgroundFor several years, cell-free DNA has been emerging as an important biomarker for non-invasive diagnostic in a wide range of clinical conditions and diseases. The limited information available on the genotoxic effects associated with occupational exposure to car paints, as well as the fact that up-to-date there are not reports about cell-free DNA measurements for assessing this condition, led us to evaluate the DNA damage caused by the occupational exposure to organic solvents contained in car paints,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
1
14
0
2
Order By: Relevance
“…The MN formation did not correlate with the ccf‐DNA amount in the blood, which might indicate different mechanisms are responsible for both parameters. A similar finding was found in a car‐paint exposed population in which ccf‐DNA and DNA damage were measured; suggesting that lack of correlation between DNA damage and ccf‐DNA can be explained by the adaptive response of ccf‐DNA and the survival mechanisms of the damaged cells [Villalba‐Campos et al, ].…”
Section: Discussionsupporting
confidence: 67%
“…The MN formation did not correlate with the ccf‐DNA amount in the blood, which might indicate different mechanisms are responsible for both parameters. A similar finding was found in a car‐paint exposed population in which ccf‐DNA and DNA damage were measured; suggesting that lack of correlation between DNA damage and ccf‐DNA can be explained by the adaptive response of ccf‐DNA and the survival mechanisms of the damaged cells [Villalba‐Campos et al, ].…”
Section: Discussionsupporting
confidence: 67%
“…Significantly elevated total cfDNA levels have been demonstrated in greenhouse workers exposed to pesticides for 5–15 years vs. controls [ 72 ], while increased cfDNA levels coupled with increased DNA damage were demonstrated in workers exposed to toxic paints in automobile paint shops [ 73 ]. Conversely, another study demonstrated a much lower level of cfDNA in nuclear-site workers exposed either to gamma-neutron or chronic tritium β-radiation [ 74 ].…”
Section: Measurement Of Total Cfdna Levels In Different Contextsmentioning
confidence: 99%
“…Furthermore, their workday may extend beyond the eight hours a day established by Colombian law, conditions that also increase the risks of genotoxic exposure. Although some studies have been conducted worldwide on this topic, including Colombia 20,23 , the relationship between the CYP2E1 polymorphisms and the presence of micronuclei in car paint shop workers have not been examined, which could be used as biomarkers of genotoxic damage and predictors of cancer risk. Consequently, it is necessary to characterize the health and work conditions of individuals occupationally exposed to organic solvents used in car paint workshops in Bogota, Colombia, to alert to the possible onset and extent of early genetic damage, as well as to identify the risk of long-term health problems and to take preventive actions aimed at promoting health.…”
Section: Open Access Introductionmentioning
confidence: 99%
“…Además, su jornada laboral puede extenderse más allá de las ocho horas diarias que establece la ley colombiana, lo que incrementa los riesgos asociados a la exposición genotóxica. A pesar de que se han desarrollado algunos estudios en diversos países del mundo sobre este tópico, incluyendo Colombia 20 , 23 , la relación entre los polimorfismos CYP2E1 y la presencia de micronúcleos en trabajadores de pintura de carros no ha sido examinada, lo que puede ser usado como un biomarcador de daño genotóxico y predictor de riesgo de cáncer. Por consiguiente, es necesario caracterizar la salud y condiciones de trabajo de individuos expuestos ocupacionalmente a solventes orgánicos usados en talleres de pintura automotriz en Bogotá, Colombia, para alertar sobre los posibles inicios de daño genético temprano, así como la identificación de los riesgos de generar problemas a largo plazo en la salud y tomar acciones preventivas que apuntan a la promoción de la salud.…”
Section: Introductionunclassified